Community Empowerment and Papaya Sauce Mixing Machine Grant in Tuah Madani Village, Tuah Madani District, Pekanbaru City - Ari Andriyas Puji; Efi Afrizal; M. Dalil; Dodi Sofyan Arief; Romy .; Iwan Kurniawan; Anggraini Dwi Saputri; Edy Fitra; Doni Saputra; Wasilah .; M. Hanif Aprilyansah; Ahmad Romadani (Faculty of Engineering UNHAS, 2026)
This research aims to improve production efficiency and product quality in the papaya sauce processing SMEs in Tuah Madani Village, Pekanbaru City, through the provision of an efficient papaya sauce mixer machine grant. These SMEs face challenges in the production process, still relying on manual methods, which lead to inconsistencies in product quality and low production capacity. This community service activity consists of two stages: socialization and the implementation of the papaya sauce mixer machine. The results of the socialization show an increase in participants' understanding of the machine technology, as measured through pre-test questionnaires. The average response indicated that 78% of the community agreed that the SMEs faced challenges such as reliance on manual stirring, limited knowledge of machines, inconsistent product quality, and difficulty in increasing production capacity. The post-test results revealed that 92% of the community agreed that the SMEs are now using a more efficient papaya sauce mixer machine, reducing dependence on manual labor, speeding up the production process, increasing both capacity and product quality, and receiving training on how to operate and maintain the machine effectively. Through the application of this technology, it is expected that the SMEs in Tuah Madani can enhance their product competitiveness, increase production capacity, and strengthen economic resilience amidst increasingly intense market competition. This technology is also expected to boost the economic activities of SMEs in a more effective and efficient manner.